Market Place-Based Online Business Competency Improvement for Online Business and Marketing MGMP Teachers throughout East Java - Veni Rafida; Harti; Tri Sudarwanto; Raya Sulistyowati; Septyan Budy Cahya (Jurnal Pengabdian Masyarakat Bestari, 2023)
This Community Service Activity (PKM) aims to improve the competence and skills of Subject Teacher Consultation (MGMP) teachers of the Online Business and Marketing Department in East Java in the field of online business, especially marketplaces. The method for implementing PKM activities is through training and mentoring: a) Designing an Online Business strategy through the Marketplace b) Designing a Marketplace. c) Designing Online promotion procedures by using/utilizing the marketplace. The results of the training are the increasing competence of teachers in teaching online business subjects and increasing the entrepreneurial spirit, which can later be seen and evaluated from the results of the training in the form of online business media that have been made, through assignments and also response questionnaires from training participants.